The effect of intrastromal PRP and oral doxycycline in corneal wound healing after alkali burn - Charalambidou, Glykeria; Kofidou, Evangelia; Papaioannou, Nikolaos; Karampatakis, Vasileios; Komnenou, Anastasia (Journal of the Hellenic Veterinary Medical Society, 2019)
Ocular chemical burns are among the most critical and true ocular emergencies in dogs and cats, with destructive consequences on the ocular surface and intraocular tissues. Platelet alpha granules are an important reservoir of growth factors that can stimulate chemotaxis of inflammatory cells, mitosis, migration and differentiation of cells. On the other hand, tetracyclines and their derivatives exhibit non-antimicrobial properties, such as affecting inflammation, immunomodulation, cell proliferation and angiogenesis. The objective of this study is to investigate the effect of intrastromal platelet rich plasma (PRP) in combination with oral doxycycline in the healing process of the cornea. Thirty six New Zealand rabbits were used in this experimental study. Alkali burns were created by applying a round filter paper soaked in NaOH. PRP was prepared by centrifugation of autologous blood. The rabbits were allocated to four groups (9 animals each). Group 1 served as the control group without any treatment. Group 2 received doxycycline (5mg/kg b.w.) orally once a day throughout the study. Group 3 received an intrastromal injection of PRP (0.5ml) in the cornea, and group 4 received intrastromal PRP combined with oral doxycycline. Treatments had varied levels of success, with PRP combined with oral doxycycline producing the best results regarding corneal healing. Animals in the control group had epithelial defects for the whole duration of the study, and 3 animals presented corneal perforation. Groups 3 and 4 had smaller mean defect area, compared to groups 1 and 2. On the 7th day, neovascularisation was lower in treatment groups compared to the control group. Groups 3 and 4 also had less corneal oedema compared to the control group on day 3 and 7. Group 4 exhibited the best wound healing, with less neovascularization and better collagen arrangement, as shown by the histopathological evaluation. To the authors’ knowledge this is the first experimental study that intrastromal PRP is combined with oral doxycycline for the management of corneal chemical burns. This combination is a simple, safe and economical therapeutic approach that promotes corneal healing.